Rocket Stove as an Eco-Friendly Waste Incinerator for Central Santan Village: Rocket Stove Sebagai Inovasi Alat Pembakaran Sampah Ramah Lingkungan Untuk Desa Santan Tengah - Yosia Dean; Yohanes Baptista; Rafael Hamonangan; Alvindra Putra; Cahya Nabila; Nur Asma; Selvi Sapitri; Madya Saputri; Stevani Dian; Muhammad Dzikry; Syebat Triana; Adi Pandu Wirawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2026)
The implementation of the Rocket Stove program in Santan Tengah Village, Marangkayu Subdistrict, Kutai Kartanegara Regency, has demonstrated its potential in addressing waste management issues, particularly organic waste, especially household waste, which is traditionally managed through open burning. This technology has the potential to be integrated into an integrated waste management system that encompasses the aspects of reduce, reuse, and recycle (3R), while also providing economic value through the utilization of the heat energy generated for the daily needs of the community. The initiative began with activities to identify community issues and needs, program planning, material and tool planning, and the construction of the rocket stove itself. Through outreach and direct demonstrations, the community demonstrated high enthusiasm for this technology, which is expected to transform waste management practices into healthier, more efficient, and sustainable ones. Success criteria are defined as: The rocket stove operates stably and safely, a reduction in dry waste volume at the testing site, positive acceptance from village officials and surrounding residents, and the establishment of Standard Operating Procedures (SOPs) and a sustainable management plan.